Mycobacterium tuberculosis PstS1 amplifies IFN‐γ and induces IL‐17/IL‐22 responses by unrelated memory CD4+ T cells via dendritic cell activation. Issue 9 (15th July 2013) - Palma, Carla; Schiavoni, Giovanna; Abalsamo, Laura; Mattei, Fabrizio; Piccaro, Giovanni; Sanchez, Massimo; Fernandez, Carmen; Singh, Mahavir; Gabriele, Lucia
<x xml:space="preserve">Abstract</x> The immunological mechanisms that modulate protection during Mycobacterium tuberculosis (Mtb) infection or vaccination are not fully understood. Secretion of IFN‐γ and, to a lesser extent, of IL‐17 by CD4+ T cells plays a major role both in protection and immunopathology. Few Mtb Ags interacting with DCs affect priming, activation, and regulation of Ag‐unrelated CD4+ T‐cell responses. Here we demonstrate that PstS1, a 38 kDa‐lipoprotein of Mtb, promotes Ag‐independent activation of memory T lymphocytes specific for Ag85B or Ag85A, two immunodominant protective Ags of Mtb. PstS1 expands CD4+ and CD8+ memory T cells, amplifies secretion of IFN‐γ and IL‐22 and induces IL‐17 production by effector memory cells in an Ag‐unrelated manner in vitro and in vivo. These effects were mediated through the stimulation of DCs, particularly of the CD8α− subtype, which respond to PstS1 by undergoing phenotypic maturation and by secreting IL‐6, IL‐1β and, to a lower extent, IL‐23. IL‐6 secretion by PstS1‐stimulated DCs was required for IFN‐γ, and to a lesser extent for IL‐22 responses by Ag85B‐specific memory T cells. These results may open new perspectives for immunotherapeutic strategies to control Th1/Th17 immune responses in Mtb infections and in vaccinations against tuberculosis.